2015
DOI: 10.1007/s10646-015-1474-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in root aeration, iron plaque formation and waterlogging tolerance in six mangroves along a continues tidal gradient

Abstract: Mangrove is a special coastal forest along tropical and subtropical intertidal shores. However, how mangroves adapt to tidal flooding and the mechanisms involved in mangrove zonation are still poorly understood. In this study, a pot trial with different tide treatments was conducted to investigate the differences in root anatomy, porosity, radial oxygen loss, iron plaque formation and waterlogging tolerance among six mangroves along a continuous tidal gradient. The index of waterlogging tolerance illustrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Hence, the trait expression of wood density should represent a classical trade-off between contrasting requirements in a stressful environment, and mangrove trees might differ in wood density (and root porosity) according to their position in the intertidal and corresponding gradients of water stress. Thus, of the six mangrove species studied by Cheng et al (2015), the order of waterlogging tolerance was Sonneratia apetala > Aegiceras corniculatum 5 Kandelia obovata > Rhizophora stylosa > Heritiera littoralis > Thespesia populnea, corresponding well with their distribution along the intertidal gradient. Thus, mid-intertidal areas are inhabited by mangrove species with low wood density and high root porosity (e.g., S. apetala, with 33% root porosity and 0.53 g cm 23 wood density), potentially maximizing O 2 acquisition.…”
Section: Wood Economics and Tree Heightmentioning
confidence: 77%
See 1 more Smart Citation
“…Hence, the trait expression of wood density should represent a classical trade-off between contrasting requirements in a stressful environment, and mangrove trees might differ in wood density (and root porosity) according to their position in the intertidal and corresponding gradients of water stress. Thus, of the six mangrove species studied by Cheng et al (2015), the order of waterlogging tolerance was Sonneratia apetala > Aegiceras corniculatum 5 Kandelia obovata > Rhizophora stylosa > Heritiera littoralis > Thespesia populnea, corresponding well with their distribution along the intertidal gradient. Thus, mid-intertidal areas are inhabited by mangrove species with low wood density and high root porosity (e.g., S. apetala, with 33% root porosity and 0.53 g cm 23 wood density), potentially maximizing O 2 acquisition.…”
Section: Wood Economics and Tree Heightmentioning
confidence: 77%
“…By contrast, the high intertidal, with less frequent inundation and lower levels of hypoxia stress, hosts species with denser wood and less porous roots. An exception to this pattern is Rhizophora mangle (exclusively AEP), which, despite exhibiting high wood density and low root porosity (Cheng et al, 2015), is very abundant in the mid intertidal. However, wood density has a strong phylogenetic signal (Swenson and Enquist, 2007), and this proves true for mangrove too (Fig.…”
Section: Wood Economics and Tree Heightmentioning
confidence: 99%
“…Here as a strategy that the roots with high aeration (e.g., a thin exodermis with low suberization together with extensive porosity and powerful ROL) can be speculated to promote soil nitrification and N uptake by mangroves. Pi et al [21] and our previous study [22,58] reported that ROL and root anatomy varied significantly among different mangrove species. It is interesting to further compare N uptake and utilization among different mangrove species in relation to root aeration and ROL.…”
Section: N Uptake By a Marina Stressed By Salt In Relation To Rol Anmentioning
confidence: 78%
“…The successe of mangrove plants is partially attributed to special anatomical structures that enable sufficient O 2 to be supplied to roots [20]. Previous studies [20][21][22] have reported that most mangroves possess extensive root porosity that provides an internal pathway and benefits O 2 transportation within the roots. During O 2 transportation within the roots, part of the O 2 may leak outside to the rhizosphere sediments simultaneously, a biological process namely radial oxygen loss (ROL) [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Rice retains a gas-associated film to facilitate oxygen uptake to survive under flooding [7]. Mangrove plants, such as Kandelia obovata, Sonneratia apetala, Aeguceras corniculatum, and Rhizophora stylosa develop specialized roots for gaseous exchange [8]. Soybean (PELBR10-6000) increased the level of CO2 assimilation rate and readily responded to the lack of energy by activating the fermentative enzymes and alanine aminotransferase during the recovering period [9], indicating that the capacity to quickly resume the normal energy level is crucial in tolerating flooding stress [10].…”
Section: Introductionmentioning
confidence: 99%